Referral patterns of special needs patients at the Royal Dental Hospital of Melbourne, Victoria, Australia. (June 2017) - Mohamed Rohani, M; Calache, H; Borromeo, GL
Abstract: Background: Special Needs Dentistry (SND) has been recognized as a dental specialty in Australia since 2003 but there have been no studies addressing the profile of patients for specialist care. The purpose of this study is to identify, via referrals received, the profile of patients and quality of referrals at the largest public SND unit in Victoria, Australia. Methods: All referrals received over a 6‐month period (1 January–30 June 2013) by the integrated SND unit (ISNU) were reviewed prior to allocation to the outpatient clinic (OP), domiciliary (DOM) or general anaesthetic (GA) services. Results: Six‐hundred and eighty‐eight referrals were received with the majority for the OP clinic (68.3%), followed by DOM (22.4%) and GA services (9.3%) (χ 2  = 360.2, P  < 0.001). A referral may have specified more than one special needs condition with the most common category being those who were medically compromised (81.7%). The reasons for referral included lack of compliance (27.2%), further management due to multiple medical conditions or GA services required (9.9%), or for multiple other reasons (62.9%). Conclusions: A diverse pattern of SND patients was referred to the ISNU with a majority of referrals having no specific referral reason cited, suggesting poor quality of referrals.